Effect of Particle Size on the Hydraulic Characteristics of Mechanically and Biologically Treated Waste. (19th September 2020) - Zhang, Zhenying; Pan, Xiufeng; Zhang, Jiahe; Xu, Hui
Abstract : Mechanical biological treatment (MBT) is a waste processing technology that helps conserve resources and reduce emissions harmful to the environment. The treatment of municipal solid waste (MSW) using MBT is a hot topic in environmental geotechnical engineering. Permeability tests were carried out on MBT waste using a compression and permeability combined apparatus and a large-scale vertical permeability apparatus taking the influence of particle size into consideration. The permeability of samples with smaller particle sizes was found to be lower for the same pressure and dry mass (%) of component. The best-fit line between the logarithmic permeability and variables such as the dry density was linear. As the dry density increased or the void ratio decreased, the permeability of samples with smaller particles decreased more. The logarithmic permeability increased with the increase in the average particle size and void ratio. The permeabilities of MBT waste corresponding to particle size ranges of 0–10, 0–20, and 0–40 mm were 10 −10 –10 −5, 10 −8 –10 −4, and 10 −5 –10 −3  m/s, respectively. The difference between MBT waste and MSW was analyzed in terms of their permeability. The results of MBT waste were compared with those reported in previous studies to provide reference for the permeability analysis of MBT landfills.